Konstruksi Realitas Petani Kelapa Sawit Dalam Film Naga Naga Naga: Analisis Semiotika Charles S. Peirce - Husni, Mochamad; Putranto, Algooth (Magister of Communication Science, Sahid University Jakarta., 2022)
The national palm oil industry is increasingly becoming the government's attention. In the midst of opinions about the dominance of big companies and the weak image of smallholder oil palm plantations, demonstrations triggered by the scarcity of cooking oil show the figure of Indonesian oil palm farmers. This study wants to explore how the media constructs the reality of oil palm farmers. The theory used is the social constructions of reality Peter L. Berger and Thomas Luckmann. While the descriptive qualitative research approach uses the semiotic analysis method of Charles Sanders Peirce. The data analysis technique used non-participant observation and secondary documents. The results of the research on the Naga Naga Naga film with the main character Nagabonar concluded that there is a semion with an interpretation of oil palm farmers. With the triangle of meaning method, oil palm farmers are constructed as people who are economically prosperous, have high nationalism, and have intelligent thoughts even though they are not formally educated. This study is also a reflection on the reality that occurs in the community.